2011
DOI: 10.1590/s0100-204x2011001000036
|View full text |Cite
|
Sign up to set email alerts
|

Dual-purpose wheat grain and animal production under different grazing periods

Abstract: -The objective of this work was to evaluate the influence of different grazing periods on beef animal production and on wheat forage and grain yield. The experiment was carried out in Pato Branco, PR, Brazil. Six grazing periods were evaluated (0, 21, 42, 63, 84, and 105 days) on dual-purpose wheat cultivar BRS Tarumã. Purunã steers, with average live weight of 162 kg and ten months of age, were kept under continuous grazing using a variable stocking rate, in order to maintain the established sward height of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
(13 reference statements)
5
6
0
Order By: Relevance
“…Menegol et al (2012) reported lower NDF results for BRS Tarumã wheat grown in the State of Rio Grande do Sul than those in this experiment. In general, the CP, NDF, and ADF levels (Tables 2 and 3) found for BRS Tarumã wheat in this study are similar to those reported by Pitta et al (2011) for an experiment conducted in the southwestern portion of the State of Paraná. 2016reported higher HEM (hemicellulose) levels in IPR 126 oat and BRS Tarumã wheat, respectively than those found in this present study.…”
Section: Resultssupporting
confidence: 89%
“…Menegol et al (2012) reported lower NDF results for BRS Tarumã wheat grown in the State of Rio Grande do Sul than those in this experiment. In general, the CP, NDF, and ADF levels (Tables 2 and 3) found for BRS Tarumã wheat in this study are similar to those reported by Pitta et al (2011) for an experiment conducted in the southwestern portion of the State of Paraná. 2016reported higher HEM (hemicellulose) levels in IPR 126 oat and BRS Tarumã wheat, respectively than those found in this present study.…”
Section: Resultssupporting
confidence: 89%
“…Also cultivation of barley led to higher profits in all periods. In another study Recent research has sought to develop crop-and grazing-management strategies for dual-purpose crops in other countries (Pitta et al, 2011;Dove and Kirkegaard, 2014). Grazing of winter wheat is a significant beef cattle production strategy in the Southern and Central Plains of the U.S. (Lollata et al, 2017).…”
Section: Agronomic Management Of Rice and Wheat To Increase Fodder Avmentioning
confidence: 99%
“…These results were superior to the productivity in this experiment. Pitta et al (2011) reported a decrease in BRS Tarumã wheat when it was grazed.…”
Section: Without Grazing One Grazing Vs Without Grazing Two Grazings mentioning
confidence: 99%